Deprivation of Inmates in Conducting Imprisonment and Guidance in Penitentiary on Victimology Perspective - Angkasa, Angkasa (Universitas Negeri Semarang, 2020)
Prisoners who undergo imprisonment tend to experience 5 (five) types of deprivation, deprivation of liberty, deprivation of goods and services, deprivation of heterosexual relationships, deprivation of heterosexual experiences, deprivation of liberty deprivation of autonomy, and deprivation of security. The research was conducted with a sociological juridical approach with a sample of Cipinang Class I Correctional Institution research sites and Banjarmasin Class II Correctional Institution as a correctional facility with prisoners' occupancy levels in excess of available capacity (overpopulation). In conditions with very high percentage of overpopulation, deprivation in the perspective of victimization has created victims in this case individual prisoners are caused because the Ministry of Law and Human Rights in this case the prison has carried out policies and actions that are not in accordance with existing provisions especially related to several provisions of Article 12 of the Republic of Indonesia Law No. 12 of 1995 Concerning Corrections, as well as the 4 (four) principles of the 10 (ten) Correctional Principles as stipulated in the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 11 of 2017 About the Grand Design Overcrowded Handling in State Detention Centers and Penitentiaries. Efforts to reduce the existence of overpopulation or overcrowded that can cause victims of human rights violations for prisoners have been carried out through the Minister of Law and Human Rights Regulation of the Republic of Indonesia Number 11 of 2017, but not yet effective.